Is My Cough a Cold or Covid? A Qualitative Study of COVID-19 Symptom Recognition and Attitudes Toward Testing in the UK - Mowbray, Fiona; Woodland, Lisa; Smith, Louise E.; Amlôt, Richard; Rubin, G. James (Frontiers in Public Health, 2021)
Objective: Key to reducing the spread of COVID-19 in the UK is increased use of the NHS Test and Trace (NHSTT) system. This study explored one of the main issues that determine whether people engage with NHSTT, how people understand symptoms that may indicate the presence of COVID-19 and that should trigger a request for a test. Methods: In this qualitative study, a series of semi-structured telephone interviews were conducted with 40 people (21 members of the general population, 19 students). There was nearly an equal split between male and female participants in both samples. Data were collected between 30 November and 11 December 2020 and explored using thematic analysis. There was substantial similarity in responses for both populations so we combined our results and highlighted where differences were present. Results: Participants generally had good knowledge of the main symptoms of COVID-19 (high temperature, new, persistent cough, anosmia) but had low confidence in their ability to differentiate them from symptoms of other illnesses. Attribution of symptoms to COVID-19 was most likely where the symptoms were severe, many symptoms were present, symptoms had lasted for some time and when perceived risk of exposure to infection was high due to previous contact with others. Participants felt encouraged to engage in testing where symptoms were present and had persisted for several days, though, many had concerns about the safety of testing centres and the accuracy of test results. Students had mixed feelings about mass asymptomatic testing, seeing it as a way to access a more normal student experience, but also a potential waste of resources. Conclusions: This study offers novel insights into how people attribute symptoms to COVID-19 and barriers and facilitators to engaging with NHSTT. Participants had positive views of testing, but there is a need to improve not just recognition of each main symptom, but also understanding that even single, mild symptoms may necessitate a test rather than a “wait and see” approach, and to address concerns around test accuracy to increase testing uptake.